Antioxidant Study of the Crude Extracts from Chromolaena odorata (L.) King & Robinson - วรานุสันติกูล, ดร.ปิยาภรณ์; โทผล, ดร.สุชาดา; แพนาค, ดร.เจษฏา; กังวานรังสรรค์, ดร. นิวัฒน์; หาญภาคภูมิ, ดร. ศรีสุดา (Journal of Food Health and Bioenvironmental Science, 2016)
Chromolaena odorata or Siam weed is a perennial herb and invasive weed commonly found throughout Thailand. It can be used in traditional medicine. Some of its medicinal properties are reported to be related to the antioxidant activity. In this study, the leaves, stems, and roots of C. odorata were subjected to extraction by various solvents and the extracts evaluated for their in vitro antioxidant activity. Extraction of leaves by water or methanol gave the highest recoveries (12.16 and 10.45%, respectively). Among the plant extracts studied, the ethanol extract of leaves showed the highest antioxidant activity in several assays. Significant differences in the amount of total phenolic content were found in extracts from different plant tissues, with the highest amount (12.1 mg GAE/mg of extract) found in ethanol extract of leaves. It can be concluded that C. odorata leaves have the highest antioxidant activities compared to other plant tissues and ethanol is the best solvent.